Indonesia enhancing productivity through quality jobs. - Ginting, Edimon (Asian Development Bank, 2018)
The challenges consist of creating jobs for and the skills in a youthful and increasingly better educated workforce, and raising the productivity of less educated workers to meet the demands of the digital age. The book deals with a range of interrelated topics the changing supply and demand for labor in relation to the shift of workers out of agriculture; urbanization and the growth of megacities; raising the quality of schooling for new jobs in the digital economy; and labor market policies to improve both labor standards and productivity.